Eating Behaviours and Body Weight Concerns among Adolescent Girls - Nadira Mallick; Subha Ray; Susmita Mukhopadhyay (Advances in Public Health)
This paper presents a global review of research done on adolescent eating behaviours and food choices and the probable factors underlying it. Worldwide adolescent girls tend to develop moderate to high level of disordered eating behaviour as a result of their excessive concern with body weight or obsession with thinness. The objective of the review is to understand the concerns over body weight and the current eating patterns of adolescent girls in the developed and developing countries.